The effect of organic fertilizer application on phytoremediation of heavy metals-contaminated rice fields using Cordyline fruticose and Excoecaria cochinchinensis - Karamina, Hidayati; Barunawati, Nunun; Kurniawan, Syahrul; Maghfoer, Moch Dawam (Journal of Degraded and Mining Lands Management, 2025)
Inadequate industrial waste management has led to heavy metal contamination in agricultural lands, threatening food productivity and sustainability. This study aimed to evaluate the effect of organic fertilizer application on the phytoremediation of heavy metals (Pb and Cd) contaminated rice fields surrounding the industrial area of Pagak, Malang Regency. The study was initiated by identifying the distribution of Pb and Cd in soil, water, and rice plants. The soil identified with the highest Pb and Cd concentrations was then subjected to a phytoremediation experiment using Cordyline fruticose and Excoecaria cochinchinensis as metal accumulator plants. Organic fertilizers used for the evaluation of the phytoremediation effectiveness were chicken manure, Thitonia, and sugarcane waste. Phytoremediation effectiveness was evaluated based on the Bioaccumulation Factor (BAF) and Translocation Factor (TF). The results of the soil characterization study showed that Pb and Cd concentrations at soil depths of 0-20 cm and 20-40 cm exceeded the permissible limits, with Pb concentrations ranging from 41.62 to 74.93 ppm and Cd concentrations ranging from 0.58 to 1.10 ppm. The results of the phytoremediation experiment showed that Cordyline fruticose exhibited higher Pb and Cd absorption capacity than Excoecaria cochinchinensis at 30 and 60 days after planting), indicated by BAF values of >1. In all treatments, however, both plant species have TF values of <1, indicating that the two plant species are considered suitable for phytostabilization as heavy metals in the soils were more concentrated in the plant roots rather than in the plant shoots.